Perceptions of risk relating to biotechnology in Australia. (1st January 2003) - Cormick, Craig
Historical comparisons to the introduction of new technologies are useful, but not always directly comparable to the introduction of biotechnology because of the complexity of different applications and the public's perceptions of risk with regard to biotechnology.